YÜKSEK VOLTAJLI ELEKTRİK YARALANMALARINDA HASTA PROFİLİ VE PRİMER TEDAVİ - AÇIKEL, Cengiz; EREN, Fikret; KALE, Bülent; ÇELİKÖZ, Bahattin (Cerrahpaşa Medical Journal, 2014)
Background and Design.- High-voltage electrical injuries causing significant morbidity and mortality have unique epidemiological and therapeutic features. Determination of high-risk groups and risk factors is vital for effective preventive measures. Besides, each burn unit should perform their own mortality and outcome analysis and compare them with other centers in order to progress the treatment protocol. This retrospective study was carried on 27 military and civilian patients with high-voltage electrical injury treated in the burn unit at Gülhane Military Medical Academy Haydarpasa Training Hospital between January 1997 and May 2001. Results.-Twenty-six of the patients were male with a mean age of 30 (14-60). Electricians and construction workers constituted the 59% of the patients. Mean total burned surface area was 13.7% (2-65) and mean length of hospital stay was 55 days (21-95). Entrance point of the electrical current was upper extremity in 89% of the patients. Sixteen major amputations were performed on 10 patients (37%). The overall mortality rate was 11%. Conclusion.- Most of the high-voltage electrical injuries occur as a result of preventable accidents. Urgent preventive measures should be taken in a well-organized and countrywide fashion. Aggressive fluid treatment, early and proper decompression, serial debridements and early definitive closure of the wounds constitute the key factors of successful therapy.